Characterization of ?-1,3-GLUCANASE gene associated with resistance to anthracnose disease in mango (Mangifera indica L.) - Petprakob, Krittika; Sang-in, Pattamon; Kitingen, Thiranai; Sertsri, Pimchanok; Sansook, Nuengtida; Nakkuntod, Maliwan (International Journal of Membrane Science and Technology, 2023)
?-1,3-Glucanase plays key roles in plants and have been studied in a wide range of plant species. It has many functions including defene plants against fungal pathogens either alone or in association with chitinases and other antifungal proteins. The structure of ?-1,3-Glucanase in mango has been incomplete. Thus, our study proposed to characterize this gene and compare DNA sequences in exon 2 of mango cultivars. The DNA was extracted from mango leaves and Colletotrichum asianum hypha, then this gene in exons 2, 3 and 4 were amplified by PCR and only sequences of exon 2 were sequenced and compared to database. The results presented that ?-1,3-Glucanase gene is composed of 4 exons which exon 2 is the largest region. Exons 2 (1254 bp) and 3 (27 bp) were interrupted by intron 2 at about 180 bp while exons 3 and 4 (153 bp) were separated with intron 3 at about 16 bp in size. Sequences in exon 2 pointed that mango in Thailand is different with mango in database from Philippine. Moreover, there were 31 SNPs in exon 2 amplified from GLU2F and GLU2R. These SNPs may be the pathogenesis-related resistance against C. asianum.